Awake Neonatal Extracorporeal Membrane Oxygenation. Issue 5 (May 2020) - Costa, Joanna; Dirnberger, Daniel R.; Froehlich, Curtis D.; Beaty, Christopher D.; Priest, Marc A.; Ogino, Mark T.
Abstract : Extracorporeal membrane oxygenation (ECMO) is used in patients with acute respiratory failure that is not responsive to conventional management. The practice of awake ECMO has become an area of interest but with limited data and experience. Most reported experience comes from adult and pediatric populations. Traditional management of these patients still includes mechanical ventilator support and often requires the use of sedatives for provision of safe care. We present a series of eight neonates who were electively extubated while on ECMO, with expanded discussion of two representative cases. We discuss the rationale for extubation and outcomes. The greatest benefit of this management was seen in patients with significant air leak, and in no reported case did we experience any adverse effects or complications as a direct result of extubation while on ECMO. In conclusion, in our experience, awake neonatal ECMO appears safe and effective and may offer significant advantages over traditional management in certain clinical scenarios. Prospective comparison trials are warranted to further investigate the clinical benefits and risks of awake neonatal ECMO.